Green analytical method for quantification of Secnidazole in tablets by HPLC-UV - Gonçalves de Souza Lima, Jéssica; Carolina Kogawa, Ana; Regina Nunes Salgado, Hérida (Drug Analytical Research, 2026)
A simple, rapid, economic and green analytical method was validated for the determination of secnidazole in tablets. The aim was to contribute to the green analytical chemistry since it has low use of organic solvent and low production of toxic waste. For the HPLC-UV method, the mobile phase was a mixture of purified water + 0.7 % acetic acid and ethanol (78:22, v/v), ﬂow rate was 1.3 mL min-1 on column CN Phenomenex Luna (250 x 4.60 mm, 5 μm particle size), injection volume was 20 μL with UV detection at 318 nm and retention time of 4.26 minutes. The method was linear over the concentration range of 5-100 μg mL-1 (r = 0.9998) with limits of detection and quantitation of 0.533 e 1.615 μg mL-1, respectively. The precision of the method showed RSD less than 2 %. The accuracy determined by the average recoveries was 99.58 %. The secnidazole tablets were subjected to oxidation, acid, alkaline, neutral and photolysis degradation as stress conditions and the method was considered as indicative of stability. The method is adequate and safe to be a great alternative method in routine quality control analyzes for determination and quantification of secnidazole tablets.